The Contestation of Islamic Boarding School Womens's View of Wifes' Rights in Poligamy - Nurnazli, Nurnazli; Ahmad, Hashm Omer; Firdawaty, Linda; al Arif, M. Yasin; Akmansyah, Muhammad (Al-Risalah, 2024)
This study examines the contention around Islamic boarding school women's view of wives' rights in polygamous marriages. It aims to answer academic questions, specifically how and why there is contention among Islamic boarding school women over the rights of wives in polygamy. Furthermore, it also aims to answer what consequences this contestation has for the practice of polygamy, which is common in Islamic boarding schools. This paper is an empirical research that takes a sociological perspective. The analysis is based on Pierre Bourdieu's Cultural Sociology theory. Data were gathered through an interview study with research subjects from five traditional Islamic boarding schools in Lampung Province. The findings of this study show that the contestation of wives' rights in polygamy is influenced by the level of understanding of religious texts and norms, social and economic realities, and the strength of the patriarchal traditions and systems that surround it. Most women are denied the opportunity to fight for their bodily and spiritual rights, both before and after polygamous marriage occurs. Women in Islamic boarding schools recognize that men's supremacy influences the neglect of women's rights in polygamy because their understanding of religious texts is conservative. Women have no bargaining power when their husbands seek to practice polygamy. Conservatives believe that polygamy is a fate and consequence that women who want to marry a caregiver or an Islamic boarding school leader (Kyai) must accept. A moderate perspective necessitates that polygamy be practiced with proportional rights between husband and wife. The repercussions of this contestation have resulted in a better appreciation of the importance of men's and women's rights being proportionate, as well as mutual protection.